Tertiary lymphoid structures in diseases: immune mechanisms and therapeutic advances - Lianyu Zhao; Song Jin; Shengyao Wang; Zhe Zhang; Xuan Wang; Zhanwei Chen; Xiaohui Wang; Shengyun Huang; Dongsheng Zhang; Haiwei Wu (Signal Transduction and Targeted Therapy, 2024)
Abstract Tertiary lymphoid structures (TLSs) are defined as lymphoid aggregates formed in non-hematopoietic organs under pathological conditions. Similar to secondary lymphoid organs (SLOs), the formation of TLSs relies on the interaction between lymphoid tissue inducer (LTi) cells and lymphoid tissue organizer (LTo) cells, involving multiple cytokines. Heterogeneity is a distinguishing feature of TLSs, which may lead to differences in their functions. Growing evidence suggests that TLSs are associated with various diseases, such as cancers, autoimmune diseases, transplant rejection, chronic inflammation, infection, and even ageing. However, the detailed mechanisms behind these clinical associations are not yet fully understood. The mechanisms by which TLS maturation and localization affect immune function are also unclear. Therefore, it is necessary to enhance the understanding of TLS development and function at the cellular and molecular level, which may allow us to utilize them to improve the immune microenvironment. In this review, we delve into the composition, formation mechanism, associations with diseases, and potential therapeutic applications of TLSs. Furthermore, we discuss the therapeutic implications of TLSs, such as their role as markers of therapeutic response and prognosis. Finally, we summarize various methods for detecting and targeting TLSs. Overall, we provide a comprehensive understanding of TLSs and aim to develop more effective therapeutic strategies.